La massification de la formation des professeurs contractuels sénégalais : formation à distance et professionnalisation - Babacar Biteye; Pascale Brandt-Pomares (Centre National d'Enseignement à Distance, 2016)
The research questions the professionalizing dimension of a distance training programme for teachers in Senegal, where they are massively recruited and have not attended any professional pre-service training. Both the activity theories as well as the professional didactics provide a relevant framework for understanding in what ways distance training facilitates the professionalization of these teachers. This conceptual framework allows us to problematize our research by considering distance training as not only a way to develop professional skills of teachers recruited without any initial training, but also as a possible means of their massive professionalization and a political determination to provide quality education. Data collection involving semi-directive interviews with different people involved in distance training provides the basis for an initial analysis aimed at clarifying the role and place of distance training in the professionalization of teachers who lack initial training.